Intertextual Femininity in the Book of Proverbs and the Dao de Jing - Schones, David A. (2020)
This essay offers an intertextual reading of Proverbs and the Dao De Jing based on the use of feminine imagery. Both the Dao De Jing and Proverbs employ feminine imagery to convey each text’s notion of the proper way. In both traditions, feminist scholars have long critiqued the ideological positions attributed to female figures. By drawing upon the diverse thematic strands in each text, the particularities of the notion of “femininity” can be explicated. Interestingly, this engagement allows the Daoist construction of the feminine to destabilize the patriarchal underpinnings of woman wisdom in Proverbs. In turn, the liberating aspects of the strong woman can be compared to, and used to critique, the conception of femininity in the Dao De Jing.